1999
DOI: 10.1289/ehp.99107911
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and air pollution as risk factors for heat stroke in Tokyo, July and August 1980-1995.

Abstract: Heat stroke is associated with prolonged exposures to high air temperatures that usually occur in the summer months of July and August in Tokyo, Japan. Also during July and August, residents of Tokyo are often exposed simultaneously to high concentrations of air pollutants. To assess the impacts of these combined exposures, daily numbers of heat stroke emergency transport cases/million residents for Tokyo were stratified by gender and three groups: 0-14, 15-64; and > 65 years of age, for the months of July and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 19 publications
(12 reference statements)
1
28
0
Order By: Relevance
“…The model for the expected daily number of emergency transports per million for each cardiovascular and respiratory disease (ET) for males and females > 65 years of age is given as ln(ET) = Xβ, [1] where X is a matrix that includes a column of 1s for the intercept; classification variable columns for sex and for annual trends; columns for the daily values for T max and/or daily average concentrations for each air pollutant variable with lag times of 1-4 days; columns for interaction effects between pairs of model covariates as indicated from the correlation analysis given in Table 3; and β is the vector of model coefficients for each model covariate. Population changes from 1980 to 1995 have been included as an offset or normalizing factor in this model so that the expected daily number of hospital emergency transports are expressed as the expected daily number of hospital emergency transports per million.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model for the expected daily number of emergency transports per million for each cardiovascular and respiratory disease (ET) for males and females > 65 years of age is given as ln(ET) = Xβ, [1] where X is a matrix that includes a column of 1s for the intercept; classification variable columns for sex and for annual trends; columns for the daily values for T max and/or daily average concentrations for each air pollutant variable with lag times of 1-4 days; columns for interaction effects between pairs of model covariates as indicated from the correlation analysis given in Table 3; and β is the vector of model coefficients for each model covariate. Population changes from 1980 to 1995 have been included as an offset or normalizing factor in this model so that the expected daily number of hospital emergency transports are expressed as the expected daily number of hospital emergency transports per million.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Previous studies have examined exposures to daily maximum temperatures and air pollutant concentrations during the warm summer months of July and August in Tokyo and their effect on the daily number of hospital emergency transports per million for heat stroke (1) and three cerebral vascular diseases: cerebral hemorrhage, cerebral infarction, and cerebral ischemia (2). Both studies indicated that males and females > 65 years of age had the highest daily number of heat stroke and cerebral vascular disease hospital emergency transports per million of any age group to four Tokyo city hospitals.…”
mentioning
confidence: 99%
“…Palavras-chave: acidente vascular cerebral, temperatura, risco cardiovascular, sazonal. The correlation between strokes and seasonal variations have been studied in various places [1][2][3][4][5][6][7][8] . Some studies around the world have reported an increase of incidence, mortality, and stroke hospitalization during the coldest months of winter.…”
mentioning
confidence: 99%
“…Qiu et al reported that an unusually hot spell in 1999 was followed by a high mortality rate in Hokkaido, Japan [12]. Piver et al showed that heat stroke was associated with prolonged exposures to higher air temperatures that usually occur in the summer months of July and August in 1980-1995 in Tokyo [13]. In our previous study, higher air temperature was closely associated with higher ambulance transports in Takamatsu and Okayama city using monthly data [3,4].…”
Section: Discussionmentioning
confidence: 84%